Medical image computing and computer-assisted intervention - MICCAI 2011 14th International Conference, Toronto, Canada, September 18-22, 2011, Proceedings, Part III - Fichtinger, Gabor; Martel, Anne; Peters, Terry (Lecture Notes in Computer Science, 2011)
The three-volume set LNCS 6891, 6892 and 6893 constitutes the refereed proceedings of the 14th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2011, held in Toronto, Canada, in September 2011. Based on rigorous peer reviews, the program committee carefully selected 251 revised papers from 819 submissions for presentation in three volumes. The third volume includes 82 papers organized in topical sections on computer-aided diagnosis and machine learning, and segmentation.